Examining the importance of digital marketing strategies in brand creation for SMEs in Malaysia - Kharmeyni Jumbulingam; Hossam Fadel; Diaa M. A. Al-Daqqaq; Caren Angellina Mimaki (Universitas Pendidikan Nasional, 2024)
This research aimed to investigate the relationship between brand creation and various types of marketing strategies in SMEs across Malaysia, with a focus on the role of digital platforms in shaping consumer engagement and perceptions. The research was conducted using a correlational quantitative approach in Malaysia. Through the probability sampling method, 51 SME employees were selected. Research data were collected through surveys and analyzed using SPSS software. The findings showed that utilizing various digital marketing strategies was essential for SME brand creation. Social media, content creation, community engagement, influencer collaboration, SEO, and email marketing proved significant in increasing brand visibility and loyalty among Malaysian consumers. The study highlighted that content marketing enabled SMEs to convey their values and unique selling propositions. Additionally, implementing an SEO strategy significantly increased an SME's visibility in search engine results, boosted website traffic, and built customer credibility. Influencer marketing was also effective for Malaysian SMEs in facilitating audience reach and increasing brand awareness through personalized consumer relationships. Moreover, email marketing played an important role in brand creation by enhancing customer relationships and engagement. This study provided empirical insights into how Malaysian SMEs leveraged digital marketing channels to strengthen their brands, emphasizing the need to adapt strategies to changing consumer preferences and technological advances in the digital landscape.